At the Heart of Learning (Series: Paper 3 of 4): Kurunta Kanyintja: Holding Knowledge in our Spirit. Issue 1 (March 2014) - Tjitayi, Katrina; Osborne, Sam
In recent years, An angu (Pitjantjatjara/Yankunytjatjara) education and remote education more broadly have strongly focused attention on key areas such as attendance and literacy and numeracy benchmarks. Remote schools have implemented a number of policies, programmes and strategies, but national statistics show that student attainment remains "behind" and the "gap" is increasing on these measures. In this paper, the authors explore the key ingredients that build confidence and "open the spirit" of young An angu students to be receptive to acquire new knowledge as they encounter new and unfamiliar experiences in school. In order to achieve this, remote educators need to consider the role of family members and the intergenerational learning environment that cements knowledge deep within the spirit. Educators are encouraged to consider the critical tools and processes required to acquire "codes of power" (Delpit, 1993), building mastery and confidence in the Western social context of schools and mainstream society.